EKSPLORASI DAN IDENTIFIKASI MIKORIZA INDIGEN ASAL TANAH BEKAS TAMBANG BATUBARA - Margarettha Margarettha (Research Center for Biology-Indonesian Institute of Sciences, 2011)
Attempts to recovery the degraded soils are applied with a friendly environment agricultural concept, such as bioremediation by potential indigenous microorganism like mycorrhyza. The objective of this research is to explore and identify indigenous mycorrhyzas of ex-mining coal soil. Soil samples were obtained as random sampling from top soil and stock pile (depth 0- 30 cm).Furthermore, identifying and trapping of mycorrhyza were also studied. The results obtained 13 types of indigenous mycorrhyzas i.e. Glomus sp. with 9 spore types, Acaulospora sp. with 3 types of and 1 type from Enthrospora sp.